Monte Carlo Simulation of Pediatric Chest Radiography: Validation of the Irradose Through Comparison with MCNP - El Bounagui, O.; Qassimi, O.; Kabach, O.; Messous, M. Y.; Tahiri, N.; Arianto, F.; El Basraoui, O. (Atom Indonesia, 2026)
Radiological examinations are essential for medical diagnostics, but accurate estimation of dose deposition is crucial for patient safety, particularly in pediatric patients. This study employs Monte Carlo simulations with the MCNP code and a newly developed custom program, Irradose, to analyze photon dose deposition in a cylindrical phantom representing the thorax of a 10-year-old child. Two tissue-equivalent compositions were modeled: water and a more realistic HCNO-based soft tissue mixture. Depth-dose distributions obtained with Irradose were compared to MCNP results. Both codes predicted a maximum dose at 2 cm depth, followed by exponential fall-off, with deviations remaining below 5% across the depth range. These results validate Irradose as a reliable and computationally efficient tool for pediatric chest dosimetry in phantom studies. While limited to simplified geometries, this work demonstrates the potential of Irradose for use in preliminary dose assessments and as a complement to established Monte Carlo codes.